A STUDY ON THE IMPACT OF SOCIAL MEDIA ON THE MENTAL HEALTH OF UNDERGRADUATE STUDENTS - Kaur, Shaminder; Bairwa, Lalita Kumari (International Journal of Research -GRANTHAALAYAH, 2025)
The present study aims to analyze the impact of social media use on the mental health and social behavior of undergraduate students. In the modern digital age, social media has become an integral part of students’ lives. Continuous online presence, exposure to various cultures, and social interactions on social media platforms have a significant impact on the mental health, social behavior, self-esteem, anxiety, stress, and emotional balance of young people. Therefore, it becomes crucial to understand whether the impact of social media on students’ mental health is positive or negative. For this study, 200 undergraduate students were selected using a random sampling technique. A ​​social media usage scale, a mental health scale, and a social behavior assessment scale were used for data collection. The collected data was analyzed using statistical techniques such as mean, standard deviation, correlation, and t-test.